(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the creation and significance of four key types of dictionaries: encyclopedic, etymological, spelling, and explanatory. It traces their historical origins, development processes, and the roles they play in language and society. Encyclopedic dictionaries combine linguistic information with detailed knowledge on various topics, serving as repositories of cultural and scientific data. Etymological dictionaries reveal the historical evolution of words, while